Determination of the piston velocity for water‐air interfaces using flux chambers, acoustic Doppler velocimetry, and IR imaging of the water surface. Issue 2 (30th May 2013) - Gålfalk, Magnus; Bastviken, David; Fredriksson, Sam; Arneborg, Lars
Abstract : [1] The transport of gasses dissolved in surface waters across the water‐atmosphere interface is controlled by the piston velocity ( k ). This coefficient has large implications for, e.g., greenhouse gas fluxes but is challenging to quantify in situ. At present, empirical k ‐wind speed relationships from a small number of studies and systems are often extrapolated without knowledge of model performance. This study compares empirical k estimates from flux chamber and surface water gas concentration measurements (chamber method), eddy cell modeling and dissipation rates of turbulent kinetic energy (dissipation method), and a surface divergence method based on IR imaging, at a fetch limited coastal observation station. We highlight strengths and weaknesses of the methods, and relate measured k values to parameters such as wave height, and surface skin velocities. The chamber and dissipation methods yielded k values in the same order of magnitude over a 24 h period with varying wind conditions (up to 10 m s −1, closest weather station) and wave heights (0.01–0.30 m). The surface divergence method most likely did not resolve the small turbulent eddies that cause the main divergence. Flux chamber estimates showed the largest temporal variability, with lower k values than the dissipation method during calm conditions, where the dissipation method failed as waves and instrument noise dominated over the turbulence signal. There was a strong correspondence between k from chambers, the RMS of surface velocities from IR imaging, and wave height. We propose a method to estimate area integrated values of k from wave measurements. Key Points: Different methods for measuring the piston velocity k were compared The chamber and dissipation k‐methods agree, except at calm conditions New k method proposed, based on strong correlation between k and wave height